EXAMINING THE IMPACT OF CLIMATE CHANGE ON ECONIMIC GROWTH IN WEST AFRICA: EVIDENCE FROM A PANEL AUTOREGRESSIVE DISTRIBUTED LAG MODEL - Choji, Niri Martha; Lar, Sohlam Peter; Kefas, David Demshark; Uji, Iordye Michael (FUDMA Journal of Sciences, 2026)
This study utilizes panel data from 2000–2022 to examine the nexus between climate change and economic growth in West Africa, employing a Panel Autoregressive Distributed Lag (ARDL) model and the Pooled Mean Group (PMG) estimator. After confirming the model’s validity through cross-sectional dependence and unit root tests, the empirical results indicate that carbon emissions and energy imports act as significant drivers of economic performance in the short run, reflecting a temporary reliance on emission-intensive activities. However, these factors, along with population growth, become statistically insignificant in the long run, suggesting that current growth models are unsustainable. With a highly significant error correction term indicating a swift return to equilibrium after shocks, the findings highlight a critical need for West African policymakers to shift toward renewable energy, enhance climate adaptation, and invest in productivity-led development to ensure durable, long-term economic stability.